Green chitosan: thiourea dioxide cleaning gel for manganese stains on granite and glass substrates - Campos, Bruno (2021)
The cleaning or removal of manganese stains on Cultural Heritage has not been much tested or successful so far. The aim of this article was to assess a new green cleaning gel for Mn-rich black-blue stains on different substrates. The black-blue stains were characterized at optical and chemical level through colour-related data, optical microscope, FTIR, XRF and XPS. Mn-stained granite found on historical churches at Vila Real (North of Portugal) and glass jars of Leclanché cells, belonging to the ISEP’s Museum (Portugal) collection, were the ideal case studies to test the efficiency of chitosan: thiourea dioxide (TD) cleaning gel. TD proved to be the best candidate to reduce insoluble manganese oxides, over Hydroxylamine Hydrochloride and Hydroxymethanesulfinic Acid. Cleaning assays performed on stained granite samples collected at a historical quarry and in situ application on stained granite churches allowed removal of the stains to a satisfactory level. Similar results were obtained on stained glass jars. © 2021, The Author(s).